The History, Development, and Challenges of Pencak Silat Pagar Nusa Cimande Style in Trenggalek 1986-2000 - Nurul Baiti Rohmah; Muhammad Zihga Iqbal Jauhari (Batuthah: Jurnal Sejarah Padaban Islam, 2026)
The establishment of Pagar Nusa by Gus Malik in 1986 was motivated by the increasing rate of juvenile delinquency and the absence of a pesantren-based martial arts organization in the Trenggalek area. This study discusses the history and development of the Cimande style of Pencak Silat Pagar Nusa in Panggul District, Trenggalek Regency, during the period 1986-2000. This study develops two focus areas, namely, the history and development of the Cimande style of Pencak Silat Pagar Nusa in Panggul, and the challenges faced in its development process. The method used is historical research through the stages of topic selection, heuristics, verification, interpretation, and historiography. The results of the study show that the Cimande style of Pagar Nusa experienced rapid development under the leadership of Mbah Djuriyat, both in terms of the number of members and the expansion of training areas. However, this school maintains challenges in the form of social stigma and competition with other silat schools that have already developed in Trenggalek. This condition requires continuous efforts to build a positive identity and image in the community.